An evaluation of HIV/AIDS knowledge and attitudes of Nkonkobe Municipality employees in the Eastern Cape province - Tyilo, Phelicia Nonzukiso (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- Stellenbosch University, 2008.